Data science and AI: Trends analysis - Aparicio, S. (2021)
This study has the primary goal to analyze the growth of data science through the main search trends. This study was conducted by defining in high level the concept of data science as well as its main components. Supported in those elements, we identified the main trends. We used mainly data from google trends to determine the evolution of search by topics., research area, or simple expressions. It allowed us to reckon that artificial intelligence (AI)suffered a lack of interest until 2012. Then it became an increasingly popular field since 2014. This is due to the progression of machine learning and data science. Results show a cumulative search of data science since 2012.